Informed Consent: How Much Awareness Is There? - Purcaru, Daniel (Public Library of Science, 2014)
Improving the informed consent process in clinical research is of constant concern to regulatory authorities in the field and presents a challenge for both the specialists and patients involved. Informed consent is a process that should adequately match the complexity of clinical research. In analyzing the behaviour of 68 patients during the informed consent process related to the clinical research performed at Neomed Clinical Center in Brasov, we found that many patients do not ask any questions (35.3%). From those who do, part of the questions (20,6%) referred to general aspects (addressed the form but not the gist) of the clinical trial, some (72,8%) referred to specific aspects of the clinical trial they will attend and others (6,6%) unrelated to the clinical trial. These results suggest a lack of interest, awareness, and understanding of the information presented in the informed consent form. The possible underlying causes of this attitude and its bureaucratic, ethic, and legal implications are discussed.